HUBUNGAN IMT DENGAN HIPERTENSI PADA LANSIA DI KELURAHAN GAYUNGAN SURABAYA - Novera Herdiani (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Hypertension is one of the number one causes of death in the world, and is the third leading cause of death after stroke and tuberculosis. BMI is very influential in the incidence of hypertension, where excessive BMI or being overweight can lead to higher risk factors for hypertension than someone with a normal BMI. The purpose of this study was to analyze the Body Mass Index (BMI) with hypertension in the elderly in Gayungan Surabaya. This study was conducted using a cross sectional method, sample selection using purposive sampling. Sample was 47 respondents. Data collection was done by measuring blood pressure, weight and height. The collected data was processed using a computer program, being analyzed by the Spearman correlation test with a significance level of α = 0.05. In this study the highest interpretation of BMI in the elderly was a normal BMI and Obes I BMI which was 14 people (29.8%). The highest criteria for hypertension were hypertension level 1 (57.4%). The sample with the highest grade 1 hypertension was normal BMI (29.79%), while the second degree hypertension was the highest in Obes I BMI (29.79%). The results of the Spearman correlation test showed that there was a significant relationship between BMI and hypertension in the elderly where p = 0.001 (p <0.05). Conclusions of this study there is a significant relationship between the interpretation of BMI and hypertension in the elderly of Gayungan Surabaya. Suggestions for older people to be more active and maintain their diet and lifestyle to prevent and control hypertension.